Cooperative routing algorithm based on game theory - Kun XIE; Shen-lin DUAN; Ji-gang WEN; Shi-ming HE (Tongxin xuebao)
Cooperative virtual multiple-input multiple-output (VMIMO) transmission is an effective technique to im-prove the transmission performance of wireless network. By taking advantage of diversity gain of VMIMO, the cross-layer VMIMO routing design combining cooperative VMIMO technology of physical layer and routing scheme of network layer can reduce power consumption of wireless transmission significantly. A significant challenge is how to make the VMIMO routing protocol robust to selfish and cheating behavior of users while guaranteeing high delivery ratio and low energy consumption. In order to improve the routing performance of selfish wireless network, a VMIMO coop-erative routing algorithm based on game theory was proposed. The network was divided into groups, and data was trans-mitted through VMIMO between groups. VMIMO routing among groups was modeled as a repeated routing game. To improve the data delivery ratio, a fit function was proposed to evaluate the nodes' credit for participating in packet for-warding. Based on the fit function, a fit value based routing selection algorithm and a fit value based routing forward al-gorithm were proposed. The proposed repeated routing game can approach to pareto optimality. Simulation result shows that this algorithm is capable of promoting cooperation between selfish nodes, which results in high delivery ratio, low transmission delay and energy consumption.